Guide plate coating for hot-rolling seamless steel pipe and preparation method of guide plate coating
Through the chemical reaction of modified basalt fibers loaded with lanthanum heteropolyacid nanoPOSS microspheres and 1,4,5,8-tetrahydroxyanthracenol, a high-temperature impact-resistant coating was constructed, which solved the problem that the silicone coating was attached to high temperatures. The problem of insufficient force and strength has achieved the improvement of high temperature stability and wear resistance of guide coatings.
Patent Information
- Application Number
- CN202411382724.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
AI Technical Summary
The existing silicone coatings have poor adhesion at high temperatures and lack of mechanical strength and toughness, making it difficult to meet the stable performance requirements of hot-rolled seamless steel pipe guide plates in high temperature and high pressure environments.
By loading nano-POSS microspheres with lanthanum heteropolyacid-doped nano-POSS microspheres on the surface of modified basalt fibers, physical interlocking and chemical bonding are formed, combining 1,4,5,8-tetrahydroxyanthracenol with silane coupling agent and high-temperature resistant silicone resin The chemical reaction of the coating is constructed to improve the high temperature, impact and wear resistance of the coating.
It significantly improves the overall structural stability and mechanical properties of the coating, enhances adhesion and wear resistance in high temperature environments, and extends the service life of the guide plate.
Smart Images

Figure CN119264809A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating preparation, and in particular relates to a guide plate coating for hot-rolled seamless steel pipes and a preparation method thereof. Background Art
[0002] Seamless steel pipe refers to a steel pipe without welds made by hot rolling, cold drawing or extrusion. During the manufacturing process, this kind of steel pipe is directly processed from solid round billet through piercing, rolling, sizing, reducing and other steps, so it has higher strength and better pressure bearing capacity. The piercing machine used in the manufacturing process of seamless steel pipe is a key equipment in the production of hot-rolled seamless steel pipe. The main function of the piercing machine is to pierce and roll the solid steel billet into a hollow rough tube, and the guide plate is an important component on the piercing machine. The main functions of the guide plate include: guiding the tube billet into the roll in the correct direction to ensure the stability and accuracy of the tube billet during the piercing process; during the piercing process, the guide plate helps to limit the lateral deformation of the tube billet and increase the closure of the hole type, thereby ensuring the uniform wall thickness and dimensional accuracy of the rough tube; the guide plate needs to withstand the impact of the high-temperature red-hot steel billet, the sliding friction under huge compressive stress and the chilling effect of cooling water, so the material of the guide plate needs to have high temperature resistance, impact resistance, wear resistance and resistance to chilling and heating. In the production process of seamless steel pipes, the use of guide plate coatings can reduce the direct contact between the rolls and the steel pipes, which can reduce the rolling force, reduce the wear of the tools, and extend the service life of the rolls. Guide plate coatings usually have excellent wear resistance, high temperature resistance and certain self-lubrication, which enable it to maintain stable performance in high temperature and high pressure working environments.
[0003] The development of heat-resistant coatings can be divided into two periods, one is inorganic heat-resistant coatings, and the other is organic heat-resistant coatings. Inorganic high-temperature resistant coatings usually use silica sol or silicate as the base material, and add metal powder or metal salts, such as zinc or aluminum zinc salts, as pigments and fillers. The base material of organic high-temperature resistant coatings is mainly organic resins with high molecular weight, but the heat-resistant temperature of organic resins is limited. Therefore, some pigments and additives with heat-resistant functions are usually added to them to prepare organic high-temperature resistant coatings. Silicone coatings are the most commonly used in high-temperature resistant coatings. Since silicone coatings have excellent performance in heat resistance, weather resistance, water resistance and insulation, silicone coatings are widely used in the field of high-temperature protection. However, silicone high-temperature resistant coatings also have the following disadvantages: the adhesion of pure silicone resins is poor, and the mechanical strength of the coatings is poor at high temperatures, such as strength, toughness and wear resistance will decrease with increasing temperature. Therefore, in order to solve the performance defects of silicone resins, it is necessary to modify their components and prepare a guide plate coating for hot-rolled seamless steel pipes. Summary of the invention
[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention realizes physical interlocking and chemical bond connection between the modified basalt fiber cloth and other components of the coating by loading nano POSS microspheres doped with lanthanum heteropoly acid on the surface of the modified basalt fiber. The coating has the advantages of high temperature resistance, impact resistance, wear resistance and resistance to cold and hot cycles.
[0005] In order to achieve the above-mentioned purpose, the following technical scheme is adopted: In the first aspect, the present invention discloses a guide plate coating for hot-rolled seamless steel pipes, comprising the following components in parts by weight: 30-60 parts of high temperature resistant silicone resin, 10-20 parts of silane coupling agent, 3-20 parts of modified basalt fiber, 3-10 parts of sodium carboxymethyl cellulose, 0.5-5 parts of dispersant, and 50-80 parts of ethanol;
[0006] Furthermore, the modified basalt fiber is prepared by the following steps:
[0007] S1, preparing a mixed acid solution with 1 mol / L sulfuric acid and 1 mol / L nitric acid in a volume ratio of 1:8-10, adding a nonionic surfactant and a water-soluble resin to the mixed acid solution, and then adding a mixed metal salt of sodium molybdate and lanthanum nitrate in a ratio of 1:0.05-0.3, and dispersing at high speed;
[0008] S2, in the dispersed solution, add octaamino POSS, continue to disperse at high speed, under ice-water bath, slowly add 1mol / L phosphoric acid, until no longer continue to produce precipitation, the generated precipitation is filtered, washed with deionized water and dried to obtain the nano POSS microspheres loaded with lanthanum heteropoly acid;
[0009] S3, drying the basalt fiber in a vacuum oven at 80°C for 2-3 hours, then soaking it in a 1 mol / L 1,4,5,8-tetrahydroxyanthraquinone ethanol solution for 2-3 hours, taking it out and drying it for later use;
[0010] S4, soaking the dried basalt fiber in a 2 mol / L sodium hydroxide ethanol solution, adding the nano POSS microspheres loaded with lanthanum heteropoly acid, ultrasonically treating the fiber at a power of 300-500 W for 10-50 min, and obtaining the modified basalt fiber after drying.
[0011] Furthermore, the mass ratio of the mixed acid solution, the nonionic surfactant, the water-soluble resin and the mixed metal salt is 100:1-3:5-10:0.5-2.
[0012] Furthermore, the nonionic surfactant is a combination of one or more of allyl polyoxyethylene ether, octylphenol polyoxyethylene ether, dodecyl alcohol polyoxyethylene ether, Span 60, Span 80, Tween 40, Tween 60 and Tween 80, preferably a combination of octylphenol polyoxyethylene ether, dodecyl alcohol polyoxyethylene ether, Span 60 and Span 80.
[0013] Furthermore, the high temperature resistant silicone resin is a combination of one or more of methyl MQ silicone resin, methyl vinyl MQ silicone resin, vinyl phenyl MQ silicone resin, epoxy modified silicone resin, polyester modified silicone resin and fluorosilicone resin, preferably a combination of vinyl phenyl MQ silicone resin, epoxy modified silicone resin and fluorosilicone resin.
[0014] Furthermore, the silane coupling agent is a combination of one or more of KH151, KH171, KH550, KH560, KH570, KH580, KH602, KH792, YDH701 and YDH702, preferably a combination of KH560, KH602 and YDH701.
[0015] Further, the dispersant is a combination of one or more of HH2800, HH2017B, Dispex AA4040, Dispex AA4140, Dispex PA4550 and Dispex PA4560, preferably a combination of HH2800, Dispex AA4040, Dispex AA4140 and Dispex PA4550.
[0016] Furthermore, the water-soluble resin is a combination of one or more of polyvinyl alcohol, polyacrylic acid, polyethylene glycol, polyacrylamide, polymethyl methacrylate and hydroxyethyl methacrylate, preferably a combination of polyethylene glycol, polymethyl methacrylate and hydroxyethyl methacrylate.
[0017] Furthermore, in step S4, the feeding amount of the nano POSS microspheres loaded with lanthanum-doped heteropoly acid is 3-8% of the mass of the sodium hydroxide ethanol solution.
[0018] Furthermore, the speed of high-speed dispersion in steps S1 and S2 is 1000-4000 rpm, and the time is 20-50 min.
[0019] In the second aspect, the present invention also discloses a method for preparing a guide plate coating for hot-rolled seamless steel pipes, the steps of which include: adding a dispersant and a high-temperature resistant silicone resin to ethanol, dispersing them by high-speed shearing, and then adding a silane coupling agent, modified basalt fiber and sodium carboxymethyl cellulose, stirring and dispersing, to obtain the guide plate coating.
[0020] The beneficial effects of the present invention are:
[0021] (1) The present invention realizes physical interlocking and chemical bond connection between the modified basalt fiber cloth and other components of the coating. The surface of the modified basalt fiber is loaded with nano POSS microspheres doped with lanthanum heteropoly acid. The nanostructure of the POSS microspheres forms physical entanglement with other components in the coating, thereby increasing the overall structural stability of the coating. 1,4,5,8-tetrahydroxyanthraquinone can react chemically with silane coupling agents, high temperature resistant organic silicone resins, etc. to form chemical bonds and three-dimensional structures, so that the coating has the advantages of high temperature resistance, impact resistance, wear resistance and resistance to cold and hot cycles, making the coating suitable for the working environment of the guide plate of the hot-rolled seamless steel pipe;
[0022] (2) the present invention first carries out lanthanum doping to phosphomolybdic heteropoly acid, increases the thermal stability of heteropoly acid by lanthanum doping, makes the phosphomolybdic heteropoly acid and nano POSS microsphere doped with lanthanum by one-step precipitation, in this process, the phosphomolybdic heteropoly acid containing defect vacancies can be stably bound on the surface of nano POSS microsphere, the siloxane group and amino group on the surface of POSS microsphere can interact with the heteropoly acid, forming chemical bond or physical adsorption, making the distribution of heteropoly acid on the surface of nano POSS microsphere more uniform and stable, the skeleton structure of nano POSS microsphere provides support and protection for heteropoly acid, prevents coating from agglomerating or losing in use, the POSS group itself has the properties of high temperature resistance, wear resistance and temperature change resistance, and the performance of nano POSS microsphere is further strengthened by the doping of lanthanum and the loading of heteropoly acid;
[0023] (3) When the basalt fiber is immersed in an ethanol solution of 1,4,5,8-tetrahydroxyanthraquinone, the 1,4,5,8-tetrahydroxyanthraquinone molecules can be attached to the surface of the basalt fiber by physical adsorption or chemical bonding. During the drying process, ethanol volatilizes to expose more active sites of 1,4,5,8-tetrahydroxyanthraquinone. These active sites can react chemically with the subsequently added nano POSS microspheres to increase the binding force between the two. The amino groups on the POSS groups react with the active hydroxyl groups of 1,4,5,8-tetrahydroxyanthraquinone to form chemical bonds, so that the loading of the nano POSS microspheres on the surface of the basalt fiber is more secure.
[0024] (4) The quinone group of 1,4,5,8-tetrahydroxyanthraquinone acts as an electrophilic center. It can combine with active groups to form new chemical bonds, and can also produce coupling or polymerization reactions with silane coupling agents and high-temperature resistant silicone resins to form a complex three-dimensional structure in the coating system, increase the crosslinking density and integrity of the coating, and improve the adhesion of the coating on the guide plate. The three-dimensional structure can better withstand external forces and improve the strength, toughness and wear resistance of the coating. Under high temperature conditions, it is conducive to the reaction between 1,4,5,8-tetrahydroxyanthraquinone and other components. At the same time, high temperature conditions and the catalytic properties of lanthanum and phosphomolybdic heteropoly acid can further promote the curing and crosslinking of the coating, thereby improving the performance stability and mechanical properties of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The mechanical properties test results of the coatings prepared in various embodiments and comparative examples of the present invention;
[0026] Figure 2 The wear resistance test results of the coatings prepared in various embodiments and comparative examples of the present invention are shown;
[0027] Figure 3 The following are SEM images of the surface microstructures of the coatings prepared in various embodiments and comparative examples of the present invention.
[0028] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0030] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0031] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.
[0032] Example 1
[0033] A guide plate coating for hot-rolled seamless steel pipe and preparation method thereof
[0034] The guide plate coating comprises the following components in parts by weight: 30 parts of high temperature resistant silicone resin, 10 parts of silane coupling agent, 3 parts of modified basalt fiber, 3 parts of sodium carboxymethyl cellulose, 0.5 parts of dispersant, and 50 parts of ethanol.
[0035] The modified basalt fiber is prepared by the following steps:
[0036] S1, prepare a mixed acid solution with 1 mol / L sulfuric acid and 1 mol / L nitric acid in a volume ratio of 1:8, add a nonionic surfactant and a water-soluble resin to the mixed acid solution, and then add a mixed metal salt of sodium molybdate and lanthanum nitrate in a ratio of 1:0.05, and disperse at a high speed of 1000 rpm for 20 minutes;
[0037] S2, in the dispersed solution, add octaamino POSS, continue to disperse at a high speed of 1000rpm for 20min, then slowly add 1mol / L phosphoric acid in an ice-water bath until no precipitation continues, filter the generated precipitation, wash with deionized water and dry to obtain nano POSS microspheres loaded with lanthanum heteropoly acid;
[0038] S3, drying the basalt fiber in a vacuum oven at 80°C for 2 hours, then soaking it in a 1 mol / L 1,4,5,8-tetrahydroxyanthraquinone ethanol solution for 2 hours, taking it out and drying it for later use;
[0039] S4, soaking the dried basalt fiber in a 2 mol / L sodium hydroxide ethanol solution, adding 3-8% of the mass of the sodium hydroxide ethanol solution to the nano POSS microspheres loaded with lanthanum-doped heteropoly acid, ultrasonically treating at a power of 300 W for 10 min, and obtaining the modified basalt fiber after drying.
[0040] The mass ratio of the mixed acid solution, the nonionic surfactant, the water-soluble resin and the mixed metal salt is 100:1:5:0.5; the nonionic surfactant is allyl polyoxyethylene ether; the high-temperature resistant silicone resin is methyl MQ silicone resin; the silane coupling agent is KH550; the dispersant is HH2800; and the water-soluble resin is polyvinyl alcohol.
[0041] The preparation method of the guide plate coating comprises: adding a dispersant and a high temperature resistant silicone resin into ethanol, dispersing them by high-speed shearing, and then adding a silane coupling agent, modified basalt fiber and sodium carboxymethyl cellulose, stirring and dispersing to obtain the guide plate coating.
[0042] Example 2
[0043] A guide plate coating for hot-rolled seamless steel pipe and preparation method thereof
[0044] The guide plate coating comprises the following components in parts by weight: 60 parts of high temperature resistant silicone resin, 20 parts of silane coupling agent, 20 parts of modified basalt fiber, 3-10 parts of sodium carboxymethyl cellulose, 5 parts of dispersant and 80 parts of ethanol.
[0045] The modified basalt fiber is prepared by the following steps:
[0046] S1, 1 mol / L sulfuric acid and 1 mol / L nitric acid are prepared into a mixed acid solution in a volume ratio of 1:10, a nonionic surfactant and a water-soluble resin are added to the mixed acid solution, and then sodium molybdate and lanthanum nitrate are added in a mixed metal salt in a ratio of 1:0.3, and high-speed dispersion is performed at a speed of 4000 rpm for 50 min;
[0047] S2, in the dispersed solution, add octaamino POSS, continue to disperse at a rotating speed of 4000rpm for 50min, then slowly drip 1mol / L phosphoric acid in an ice-water bath until no precipitation continues, filter the generated precipitation, wash with deionized water and dry to obtain the nano POSS microspheres loaded with lanthanum heteropoly acid;
[0048] S3, drying the basalt fiber in a vacuum oven at 80°C for 3 hours, then soaking it in a 1 mol / L 1,4,5,8-tetrahydroxyanthraquinone ethanol solution for 3 hours, taking it out and drying it for later use;
[0049] S4, soaking the dried basalt fiber in a 2 mol / L sodium hydroxide ethanol solution, adding 8% of the mass of the sodium hydroxide ethanol solution to the nano POSS microspheres loaded with lanthanum-doped heteropoly acid, ultrasonically treating at a power of 500 W for 50 min, and obtaining the modified basalt fiber after drying.
[0050] The mass ratio of the mixed acid solution, the nonionic surfactant, the water-soluble resin and the mixed metal salt is 100:3:10:2; the nonionic surfactant is octylphenol polyoxyethylene ether; the high-temperature resistant silicone resin is vinyl phenyl MQ silicone resin; the silane coupling agent is KH602; the dispersant is HH2017B; and the water-soluble resin is polyethylene glycol.
[0051] The preparation method of the guide plate coating is the same as that of Example 1.
[0052] Example 3
[0053] A guide plate coating for hot-rolled seamless steel pipe and preparation method thereof
[0054] The guide plate coating comprises the following components in parts by weight: 40 parts of high temperature resistant silicone resin, 12 parts of silane coupling agent, 8 parts of modified basalt fiber, 6 parts of sodium carboxymethyl cellulose, 1 part of dispersant, and 60 parts of ethanol.
[0055] The modified basalt fiber is prepared by the following steps:
[0056] S1, prepare a mixed acid solution with 1 mol / L sulfuric acid and 1 mol / L nitric acid in a volume ratio of 1:8.5, add a nonionic surfactant and a water-soluble resin to the mixed acid solution, and then add a mixed metal salt of sodium molybdate and lanthanum nitrate in a ratio of 1:0.1, and disperse at a high speed of 2000 rpm for 40 minutes;
[0057] S2, in the dispersed solution, add octaamino POSS, continue to disperse at a rotating speed of 3000rpm for 50min, then slowly add 1mol / L phosphoric acid in an ice-water bath until no precipitation is produced, filter the generated precipitation, wash with deionized water and dry to obtain the nano POSS microspheres loaded with lanthanum heteropoly acid;
[0058] S3, drying the basalt fiber in a vacuum oven at 80°C for 2 hours, then soaking it in a 1 mol / L 1,4,5,8-tetrahydroxyanthraquinone ethanol solution for 2.5 hours, taking it out and drying it for later use;
[0059] S4, soaking the dried basalt fiber in a 2 mol / L sodium hydroxide ethanol solution, adding 5% of the mass of the sodium hydroxide ethanol solution to the nano POSS microspheres loaded with lanthanum heteropoly acid, ultrasonically treating at a power of 350 W for 30 min, and obtaining the modified basalt fiber after drying.
[0060] The mass ratio of the mixed acid solution, the nonionic surfactant, the water-soluble resin and the mixed metal salt is 100:2:6:1.5; the nonionic surfactant is dodecyl alcohol polyoxyethylene ether; the high-temperature resistant silicone resin is fluorosilicone resin; the silane coupling agent is KH570; the dispersant is Dispex AA4040; and the water-soluble resin is polyacrylamide.
[0061] The preparation method of the guide plate coating is the same as that of Example 1.
[0062] Example 4
[0063] The difference between this embodiment and embodiment 3 is as follows:
[0064] The nonionic surfactant is a combination of octylphenol polyoxyethylene ether, dodecyl alcohol polyoxyethylene ether, Span 60 and Span 80 in a mass ratio of 2:1:3; the high temperature resistant silicone resin is a combination of vinyl phenyl MQ silicone resin, epoxy modified silicone resin and fluorosilicone resin in a mass ratio of 3:3:5; the silane coupling agent is a combination of KH560, KH602 and YDH701 in a mass ratio of 3:2:3; the dispersant is a combination of HH2800, Dispex AA4040, Dispex AA4140 and Dispex PA4550 in a mass ratio of 2:2:3:5; the water-soluble resin is a combination of polyethylene glycol, polymethyl methacrylate and hydroxyethyl methacrylate in a mass ratio of 2:1:2.5.
[0065] The remaining components, proportions and preparation process are the same as those in Example 3.
[0066] Example 5
[0067] The difference between this embodiment and embodiment 3 is as follows:
[0068] The high temperature resistant silicone resin is a combination of methyl MQ silicone resin, epoxy modified silicone resin and polyester modified silicone resin in a mass ratio of 3:3:5.
[0069] The remaining components, proportions and preparation process are the same as those in Example 3.
[0070] Example 6
[0071] The difference between this embodiment and embodiment 3 is as follows:
[0072] The water-soluble resin is a combination of polyvinyl alcohol, polyacrylic acid and polyethylene glycol in a mass ratio of 2:1:2.5.
[0073] The remaining components, proportions and preparation process are the same as those in Example 3.
[0074] Comparative Example 1
[0075] The difference between this comparative example and Example 4 is that the basalt fiber is not modified, that is, an equal amount of basalt fiber is used to replace the modified basalt fiber, and the rest is the same as Example 4.
[0076] Comparative Example 2
[0077] The difference between this comparative example and Example 4 is that the heteropoly acid is not doped with lanthanum, that is, lanthanum nitrate is not added in step S1, and the rest is the same as Example 4.
[0078] Comparative Example 3
[0079] The difference between this comparative example and Example 4 is that the nano POSS microspheres are not loaded with heteropolyacid, and the rest are the same as Example 4.
[0080] The modified basalt fiber is prepared by the following steps:
[0081] S1. Prepare a mixed acid solution by mixing 1 mol / L sulfuric acid and 1 mol / L nitric acid in a volume ratio of 1:8-10, add a nonionic surfactant and a water-soluble resin to the mixed acid solution, and perform high-speed dispersion;
[0082] S2, adding octaamino POSS to the dispersed solution, continuing to disperse at high speed, filtering the generated precipitate, washing with deionized water and drying to obtain nano POSS microspheres;
[0083] S3, drying the basalt fiber in a vacuum oven at 80°C for 2-3 hours, then soaking it in a 1 mol / L 1,4,5,8-tetrahydroxyanthraquinone ethanol solution for 2-3 hours, taking it out and drying it for later use;
[0084] S4, soaking the dried basalt fiber in a 2 mol / L sodium hydroxide ethanol solution, adding the nano POSS microspheres loaded with lanthanum-doped heteropoly acid, and then ultrasonically treating the fiber for 30-60 min, and obtaining the modified basalt fiber after drying.
[0085] The mass ratio of the nano POSS microspheres is the same as that of the nano POSS microspheres loaded with lanthanum-doped heteropoly acid in Example 4.
[0086] Comparative Example 4
[0087] The difference between this comparative example and Example 4 is that the basalt fiber is not immersed in the ethanol solution of 1,4,5,8-tetrahydroxyanthraquinone, and the rest is the same as Example 4.
[0088] The modified basalt fiber is prepared by the following steps:
[0089] S1, preparing a mixed acid solution with 1 mol / L sulfuric acid and 1 mol / L nitric acid in a volume ratio of 1:8-10, adding a nonionic surfactant and a water-soluble resin to the mixed acid solution, and then adding a mixed metal salt of sodium molybdate and lanthanum nitrate in a ratio of 1:0.05-0.3, and dispersing at high speed;
[0090] S2, in the dispersed solution, add octaamino POSS, continue to disperse at high speed, under ice-water bath, slowly add 1mol / L phosphoric acid, until no longer continue to produce precipitation, the generated precipitation is filtered, washed with deionized water and dried to obtain the nano POSS microspheres loaded with lanthanum heteropoly acid;
[0091] S3, drying the basalt fiber in a vacuum oven at 80° C. for 2-3 h, then soaking it in a 2 mol / L sodium hydroxide ethanol solution, adding the nano POSS microspheres loaded with lanthanum-doped heteropoly acid, and then ultrasonically treating it for 30-60 min, and obtaining the modified basalt fiber after drying.
[0092] Test Example 1
[0093] Coating mechanical properties test
[0094] The mechanical properties of the coating were tested by INSTRON 6800 electronic universal material testing machine. The sample size was 75 ± 0.1 mm in total length, 2 ± 0.1 mm in thickness, and 4 ± 0.2 mm in width. Three standard samples were used each time and the average value was calculated. The results are shown in Figure 1 .
[0095] pass Figure 1 It can be seen from the test results that the tensile properties and high strain capacity of the coating of the present invention are greatly improved compared with the comparative examples. The improvement of the tensile properties and high strain capacity of the coating means that the coating can better resist deformation when subjected to tensile force, and exhibits excellent toughness and mechanical properties. Under high temperature and mechanical stress environments, the guide plate coating needs to maintain its structural integrity and functional performance. Therefore, excellent toughness and mechanical properties are very important for the guide plate coating of hot-rolled seamless steel pipes. The improved tensile properties and strain capacity help the coating to withstand thermal and mechanical stresses during the operation of the guide plate, reduce the breakage and shedding of the coating, and thus extend the service life of the guide plate.
[0096] Test Example 2
[0097] Paint abrasion resistance test
[0098] The falling sand abrasion resistance test was carried out according to the test method of GB / T 23988-2009. The results are shown in Figure 2 .
[0099] pass Figure 2 The test results show that the coating of the present invention exhibits excellent wear resistance, indicating that during the long-term use of the hot-rolled seamless steel pipe guide plate, the coating can effectively resist wear and reduce material loss, thereby extending the service life of the guide plate. In a high temperature and wear environment, good wear resistance can protect the guide plate from erosion by wear particles, maintain the smooth surface of the guide plate, and reduce production interruptions and maintenance work caused by wear.
[0100] Test Example 3
[0101] Coating physical and chemical properties test
[0102] include:
[0103] Heat resistance test: According to the test method of GB / T 1735-2009, heat the cured sample in a high temperature furnace at 850℃ for 24h, observe the coating film, and it is qualified if there is no cracking or shedding on the surface;
[0104] Adhesion test: According to the test method of GB / T 9286-1998, use a grid knife to cut the coating at a uniform speed, so that the cut can penetrate the fire retardant coating and cut to the surface of the substrate, then rotate the blade 90 degrees to form a grid pattern, then use a soft brush to clean the debris generated in the test area, and use tape to stick the test grid and press hard;
[0105] Hardness test: Tested according to the coating hardness pencil test method of GB / T 6739-2006;
[0106] Water resistance test: The water resistance is measured according to the test method of GB / T 1733-1993. The cured fire retardant coating is sealed with a mixture of paraffin wax and rosin. The sealing width is not less than 5mm. 2 / 3 of the test panel covered with the coating is placed in 25℃ deionized water. Record once a day to observe whether the coating surface is bubbling or falling off.
[0107] Resistance to cold and heat cycles test: place the sample at room temperature for 18 hours, then place it in a -20 low temperature box for 1 hour, and then place it in a 200 constant temperature box for 1 hour. Repeat the above operation 15 times. The coating is considered qualified if there is no cracking or falling off. At least 2 of the 3 samples must be qualified. The resistance to cold and heat cycles of the coating is evaluated by the number of cycles.
[0108] Table 1 Test results of coating physical and chemical properties
[0109]
[0110]
[0111] It can be seen from the test results in Table 1 that the physical and chemical properties of the coatings prepared by the embodiments of the present invention are better than those of the comparative examples. The coating of the present invention forms a three-dimensional structure with excellent heat resistance by using 1,4,5,8-tetrahydroxyanthraquinone and a high temperature resistant organic silicone resin. This structure can remain stable under high temperature conditions, thereby ensuring that the coating is not easy to decompose or degrade in the high temperature working environment of the hot-rolled seamless steel pipe guide plate. The amino groups of the silane coupling agent and nano POSS microspheres in the coating form chemical bonds with the 1,4,5,8-tetrahydroxyanthraquinone on the surface of the basalt fiber, thereby enhancing the adhesion between the coating and the substrate, ensuring that the coating is not easy to peel off during use, and improving the durability and reliability of the guide plate. With the addition of the balls, the crosslinking density of the coating is improved, thereby increasing the hardness of the coating film. The increase in hardness helps to resist the intrusion and scratches of foreign objects and maintain the integrity and functionality of the guide plate surface. The increase in hardness also corresponds to the results of the wear resistance test in Example 2. The guide plate will be in contact with cooling water during actual work, and the cooling water will help cool the steel pipe or clean the rollers. The lanthanum-doped phosphomolybdic acid and POSS microspheres in the coating provide good water resistance and resistance to cold and hot cycles, which means that the coating can remain stable under rapid changes in temperature without cracks or peeling. Therefore, the coating prepared by the present invention can enhance the durability and reliability of the guide plate, and help improve the efficiency and safety of the entire hot-rolled seamless steel pipe production line.
[0112] Test Example 4
[0113] Observation of coating surface microstructure
[0114] The coating was applied to the steel plate by brush and cured at room temperature for 7 days. The surface morphology of the coating was observed by scanning electron microscope. The SEM images of the observation results are shown in Figure 3 ,Depend on Figure 3 It can be seen that the surface of the coating of Example 4 is relatively dense and smooth, proving that the coating film surface layer of the coating is complete and uniform, while the coating of the comparative example has different degrees of agglomeration and the surface is rough and uneven. The rough and uneven coating film will reduce the wear resistance and temperature resistance of the coating, which corresponds to the test results of the aforementioned embodiments.
[0115] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
[0116] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A guide plate coating for hot-rolled seamless steel pipes, characterized in that: The invention comprises the following components in parts by weight: 30-60 parts of high temperature resistant silicone resin, 10-20 parts of silane coupling agent, 3-20 parts of modified basalt fiber, 3-10 parts of sodium carboxymethyl cellulose, 0.5-5 parts of dispersant, and 50-80 parts of ethanol; The modified basalt fiber is prepared by the following steps: S1, preparing a mixed acid solution with 1 mol / L sulfuric acid and 1 mol / L nitric acid in a volume ratio of 1:8-10, adding a nonionic surfactant and a water-soluble resin to the mixed acid solution, and then adding a mixed metal salt of sodium molybdate and lanthanum nitrate in a ratio of 1:0.05-0.3, and dispersing at high speed; S2, in the dispersed solution, add octaamino POSS, continue to disperse at high speed, under ice-water bath, slowly add 1mol / L phosphoric acid, until no longer continue to produce precipitation, the generated precipitation is filtered, washed with deionized water and dried to obtain the nano POSS microspheres loaded with lanthanum heteropoly acid; S3, drying the basalt fiber in a vacuum oven at 80°C for 2-3 hours, then soaking it in a 1 mol / L 1,4,5,8-tetrahydroxyanthraquinone ethanol solution for 2-3 hours, taking it out and drying it for later use; S4, soaking the dried basalt fiber in a 2 mol / L sodium hydroxide ethanol solution, adding the nano POSS microspheres loaded with lanthanum heteropoly acid, ultrasonically treating the fiber at a power of 300-500 W for 10-50 min, and obtaining the modified basalt fiber after drying.
2. The guide plate coating for hot-rolled seamless steel pipe according to claim 1, characterized in that: The mass ratio of the mixed acid solution, the nonionic surfactant, the water-soluble resin and the mixed metal salt is 100:1-3:5-10:0.5-2.
3. The guide plate coating for hot-rolled seamless steel pipe according to claim 1, characterized in that: The nonionic surfactant is a combination of one or more of allyl polyoxyethylene ether, octylphenol polyoxyethylene ether, dodecyl alcohol polyoxyethylene ether, Span 60, Span 80, Tween 40, Tween 60 and Tween 80.
4. The guide plate coating for hot-rolled seamless steel pipe according to claim 1, characterized in that: The high temperature resistant silicone resin is a combination of one or more of methyl MQ silicone resin, methyl vinyl MQ silicone resin, vinyl phenyl MQ silicone resin, epoxy modified silicone resin, polyester modified silicone resin and fluorosilicone resin.
5. The guide plate coating for hot-rolled seamless steel pipe according to claim 1, characterized in that: The silane coupling agent is a combination of one or more of KH151, KH171, KH550, KH560, KH570, KH580, KH602, KH792, YDH701 and YDH702.
6. The guide plate coating for hot-rolled seamless steel pipe according to claim 5, characterized in that: The dispersant is a combination of one or more of HH2800, HH2017B, Dispex AA4040, Dispex AA4140, Dispex PA4550 and Dispex PA4560.
7. The guide plate coating for hot-rolled seamless steel pipe according to claim 1, characterized in that: The water-soluble resin is a combination of one or more of polyvinyl alcohol, polyacrylic acid, polyethylene glycol, polyacrylamide, polymethyl methacrylate and hydroxyethyl methacrylate.
8. The guide plate coating for hot-rolled seamless steel pipe according to claim 1, characterized in that: In the step S4, the feeding amount of the nano POSS microspheres loaded with lanthanum-doped heteropoly acid is 3-8% of the mass of the sodium hydroxide ethanol solution.
9. The guide plate coating for hot-rolled seamless steel pipe according to claim 1, characterized in that: The speed of high-speed dispersion in steps S1 and S2 is 1000-4000 rpm, and the time is 20-50 min.
10. A method for preparing a guide plate coating for hot-rolled seamless steel pipe according to any one of claims 1 to 9, characterized in that: The guide plate coating is obtained by adding a dispersant and a high temperature resistant silicone resin into ethanol and dispersing them by high-speed shearing, then adding a silane coupling agent, modified basalt fiber and sodium carboxymethyl cellulose, stirring and dispersing them.
Citation Information
Patent Citations
Method for preparing graphite oxide-based aperture adjustable nano porous material
CN101734653A
Preparation of phosphomolybdate catalyst loaded on gamma-Al2O3
CN102764668A
Boron-modified organic silicon resin high-temperature-resistant coating and preparation method thereof
CN104212347A
Waterborne durable antibacterial purification coating as well as preparation method and application thereof
CN118222128A
Cited By
High-temperature-resistant fireproof coating based on basalt scales and preparation method of high-temperature-resistant fireproof coating
CN121064728A